2014
DOI: 10.1007/s13244-014-0309-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography for clinical decision-making and intervention in airway management: from the mouth to the lungs and pleurae

Abstract: ObjectivesTo create a state-of-the-art overview of the new and expanding role of ultrasonography in clinical decision-making, intervention and management of the upper and lower airways, that is clinically relevant, up-to-date and practically useful for clinicians.MethodsThis is a narrative review combined with a structured Medline literature search.ResultsUltrasonography can be utilised to predict airway difficulty during induction of anaesthesia, evaluate if the stomach is empty or possesses gastric content t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
74
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 243 publications
0
74
0
14
Order By: Relevance
“…Moreover emergency departments, Meta-analysis Reports also revealed the sensitivity of 78.6-90.9 % and specif icity of 98.2-98.4 % for US which chests radiographs had showed sensitivity of 39.8-50.2 % and specif icity of 99.3-99.4 % (Alrajhi 2012; Alrajab ., 2013). Lung sliding, B-lines, lung pulse, and lung point are some features which can help pneumothorax to be detected or omitted by the US (Volpicelli , 2012).Lung sliding or B-lines can exclude pneumothorax when we report them on the anterior surface of a supine patient's chest (Lichtenstein 2005;Soldati , 2008;Ebrahimi , 2014;Kristensen , 2014;Obrador 2014). A meta-analysis by Ebrahimi (2014) indicated that the diagnostic accuracy of US was higher than supine CXR for diagnosis of pneumothorax.…”
Section: Thoracentesismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover emergency departments, Meta-analysis Reports also revealed the sensitivity of 78.6-90.9 % and specif icity of 98.2-98.4 % for US which chests radiographs had showed sensitivity of 39.8-50.2 % and specif icity of 99.3-99.4 % (Alrajhi 2012; Alrajab ., 2013). Lung sliding, B-lines, lung pulse, and lung point are some features which can help pneumothorax to be detected or omitted by the US (Volpicelli , 2012).Lung sliding or B-lines can exclude pneumothorax when we report them on the anterior surface of a supine patient's chest (Lichtenstein 2005;Soldati , 2008;Ebrahimi , 2014;Kristensen , 2014;Obrador 2014). A meta-analysis by Ebrahimi (2014) indicated that the diagnostic accuracy of US was higher than supine CXR for diagnosis of pneumothorax.…”
Section: Thoracentesismentioning
confidence: 99%
“…The pooled sensitivity and specif icity of CXR were 0.46 and 1.0, respectively. A study by Kristensen (2014) showed that Ultrasonography is a reliable device for intraoperative and emergency diagnosis of pneumothorax. The US provide us diagnosis and management of interstitial syndrome, lung consolidation, atelectasis, pleural effusion and differentiate etiologies of acute breathlessness during pregnancy.…”
Section: Thoracentesismentioning
confidence: 99%
“…The literature has reported numerous cases (concerning as much as 27% of study participants) in which SpO 2 in mothers dropped to 91−92% and the use of oxygen was necessary [4]. In recent years even more alarming reports have been published.…”
mentioning
confidence: 99%
“…Airway ultrasound, which is a simple and noninvasive procedure, enables visualisation of the larynx and trachea and can help perform tracheotomy in very "difficult" patients. Ultrasound of the larynx and trachea is recommendable in all patients with potential difficult airway [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation